ANALISIS PERAN PETUGAS AVIATION SECURITY (AVSEC) DALAM PEMERIKSAAN PENUMPANG DAN BARANG PADA ERA NEW NORMAL DI BANDAR UDARA H. ASAN SAMPIT KALIMANTAN TENGAH - Wahyu Indro Prasetyo; Rosiana Ulfa (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
During the Covid-19 virus outbreak, there were many obstacles faced by aviation companies, especially the Aviation Security Unit (Avsec) as the spearhead in maintaining flight security and safety. Aviation security must carry out its duties seriously and thoroughly by obeying flight rules, especially those relating to passengers and goods especially in the new normal era, so that the Covid-19 virus does not spread further. The purpose of this research is to find out the role of aviation security officers (Avsec) and what factors are the obstacles in inspecting passengers and goods during the new normal era at H. Asan Sampit airport, Central Kalimantan. This study used a qualitative method in which data was collected by interviewing several Avsec officers, observing the work area of the Avsec unit, and documenting data in the form of SOP or work procedures. Data analysis techniques in this study include data collection, data reduction, and conclusions. The results of the study show that the role of Avsec officers in the new normal era is basically the same as officers who maintain the security and safety of passengers from acts against the law but pay more attention to the health of passengers and officers so they don't participate in spreading the Covid-19 virus, and there are health protocols that become a new habit for the community after the pandemic. Obstacles faced by officers in inspecting passengers and goods in the new normal era include the lack of awareness of passengers about the rules that have been set. Another obstacle is passenger inspection which is less than optimal due to minimizing physical contact to prevent the spread of Covid-19.